Western Slavs and the cult of Cyril and Methodius - Yurgova Komsalova, Rumyana (Balcanica Posnaniensia. Acta et studia, 2009)
The aim of the article is to specify the characteristics of the formation and development of the cult of Cyril and Methodius among the Western Slavs and to analyse the mechanisms of adaptation of their heritage in the Catholic and Orthodox traditions. The author attempts to show how the memory of the brothers changed depending on political, religious and cultural conditions. The methodological basis is a historical and philological analysis of written sources – lives, legends, liturgical texts, Latin and Slavic chronicles. The use of original medieval monuments and later accounts allows us to trace the evolution of the images of both saints. The cult of Cyril and Methodius took on a universal character, going beyond the framework of a separate ethnic or religious tradition. For the Western Slavs, it became an important element of cultural memory, despite the gradual replacement of the Slavic liturgy by the Latin one. Over time, legends surrounded the real historical figures, which contributed to the transformation of Cyril and Methodius into saints equal to the apostles, venerated in both the Orthodox and Catholic worlds.